DNA barcoding identifies three species of croakers (Pisces, Sciaenidae) in the ichthyoplankton of the High Paraná River - Briñoccoli, Yanina Florencia (2020)
In the province of Misiones (Argentina), the filling of the Yacyretá Reservoir (Argentina-Paraguay) to its final dimensions in 2011 formed new aquatic ecosystem, e.g., Garupá Stream was converted into a subreservoir. Reports have been made in this stream of adult individuals and spawning of the Family Sciaenidae, excellent colonizers of modified environments. The larvae of this family are morphologically similar, particularly among Pachyurus and Plagioscion species, making taxonomic differentiation difficult. In the present work, sciaenidae larvae were characterized molecularly at the cytochrome c oxidase subunit I gene in order to determine which species use this environment for reproduction. Additionally, genetic distances, Barcode Index Number (BIN) and Automatic Barcode Gap Discovery method (ABGD) were estimated and phylogenetic trees were reconstructed. The results indicated the presence of Plagioscion ternetzi and Pachyurus bonariensis larvae, and for the first time in tributaries of the region, Plagioscion squamosissimus. The incorporation of P. bonariensis and P. squamosissimus to the faunistic assemblage of ichthyoplankton in the Garupá Stream supports better characterization of the species richness of this secondary watercourse modified by the Yacyretá Reservoir, and advancement in our understanding of use of this area for reproduction.